Comparing inflation and price-level targeting: A comprehensive review of the literature - Michael C. Hatcher (Cardiff University, Cardiff Business School, 2011)
This paper provides a detailed survey of the economic literature comparing inflation and price-level targeting as macroeconomic stabilisation policies. Its contributions relative to past surveys are as follows. First, rather than focusing on any particular topic, the survey gives equal emphasis to all key areas of the literature. Second, the paper discusses 'new results' in several areas, including the zero lower bound on nominal interest rates; the long-term impact of price-level targeting; and financial market considerations. Finally, the survey is written in such a way that it can be understood by economists with little or no prior knowledge of price-level targeting and the related academic literature. The survey concludes that whilst price-level targeting has a number of potential advantages, further research is needed to accurately quantify its costs and benefits and to test robustness. Potential obstacles to the introduction of price-level targeting in practice include: concerns about its credibility; lack of public understanding; and lack of prior experience with price-level targeting regimes.
Keywords: E52; E58; 330; price-level targeting; inflation targeting; macroeconomic stabilisation; Wirtschaftslage; Inflationsrate; Inflation Targeting; Zinspolitik; Bibliometrie